Government Geoscience Stimulates Mineral Exploration in the Superior Province, Northern Québec - Leclair, Alain; Labbé, Jean-Yves; Berclaz, Alain; David, Jean; Gosselin, Charles; Lacoste, Pierre; Madore, Louis; Maurice, Charles; Roy, Patrice; Sharma, Kamal; Simard, Martin (Geoscience Canada, 2006)
SUMMARY This paper summarizes new geologic information, and highlights exploration opportunities in the northeastern part of the Superior Province since 1997, as a result of the Far North Program undertaken by Géologie Québec. The first phase of the program was a regional lake-sediment geochemical survey, where 26,000 samples were collected north of 55°N from an area of approximately 350,000 km2. The resulting database attracted many mining companies to the region and led to numerous mineral discoveries. The second phase, started in 1998, consisted of extensive geological mapping, supplemented by U-Pb geochronological work; by 2003, more than twenty, 1:250,000 mapping projects were completed. The Far North Program is now in its final phase and it will produce a comprehensive geological and metallogenic synthesis of the new data from the areas surveyed. About forty previously unknown volcano-sedimentary belts, numerous mafic-ultramafic intrusions and sixteen different mineral deposit types have been identified. Since 1997, this has resulted in a surge of exploration activity that has seen more than $38 million in expenditures by private industry.